2016
DOI: 10.1136/bmjquality.u210642.w4280
|View full text |Cite
|
Sign up to set email alerts
|

The use of a pro forma to improve quality in clerking vascular surgery patients

Abstract: At our institution, a large tertiary referral centre for vascular surgery, patients are often admitted directly to the ward and clerked by foundation year one (FY1) doctors. We found that these clerkings frequently fell short of national record keeping standards, potentially leading to an increased risk for patients during their hospital stay. In addition, we found that junior doctors did not feel confident in clerking vascular surgery patients.A literature review found that high quality clerkings were strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…However often the clerking doctor may not be the surgeon performing the procedure and can be a relatively junior grade who is working under significant time or work pressure (4). These pressures have been noted to result in poor documentation and missed elements of admission notes (5) which can render important documentation such as consent forms substandard or even invalid (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However often the clerking doctor may not be the surgeon performing the procedure and can be a relatively junior grade who is working under significant time or work pressure (4). These pressures have been noted to result in poor documentation and missed elements of admission notes (5) which can render important documentation such as consent forms substandard or even invalid (4).…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of consent documentation for common trauma procedures have found poor documentation of risks (8) often with a wide variety of complications listed for the same procedure in varying frequencies (9). These deficiencies in documentation have been attributed to not only the aforementioned work pressures but also poor overall awareness of local or national guidelines and standards (10), which is often exacerbated by a relatively rapid turnover of junior staff (rotating as frequently as every 4 months) (5). This is despite Department of Health and Royal College of Surgeons guidelines on consent that state the person obtaining consent should have clear knowledge of the procedure along with the potential risks and complications (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…However often the clerking doctor may not be the surgeon performing the procedure and can be a junior grade physician who is working under signi cant time or work pressure (4). These pressures have been noted to result in poor documentation and missed elements of admission notes (5) which can render important documentation such as consent forms substandard or even invalid (4).…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of consent documentation for common trauma procedures have found poor documentation of risks (8) often with a wide variety of complications listed for the same procedure in varying frequencies (9). These de ciencies in documentation have been attributed to not only the aforementioned work pressures but also poor overall awareness of local or national guidelines and standards (10), which is often exacerbated by a relatively rapid turnover of junior staff (rotating as frequently as every 4 months) (5). This is despite Department of Health and Royal College of Surgeons guidelines on consent that state the person obtaining consent should have clear knowledge of the procedure along with the potential risks and complications (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Various departments have now devised their own specific performa which has sections to be filled with key history points. [2][3][4][5] Problem based learning (PBL) in various ways has become popular in medical schools over the past few years. There was serious division seen between the supporters and the skeptics when the teaching patterns was switched for the first time, and serious concerns were seen regarding the quality and level of knowledge being conveyed to the students.…”
Section: Introductionmentioning
confidence: 99%